Synthesis, characterization, and immune efficacy of layered double hydroxide@SiO(2) nanoparticles with shell-core structure as a delivery carrier for Newcastle disease virus DNA vaccine - Zhao, Kai (Int J Nanomedicine, 2015)
Layered double hydroxide (LDH)@SiO(2) nanoparticles were developed as a delivery carrier for the plasmid DNA expressing the Newcastle disease virus F gene. The LDH was hydrotalcite-like materials. The plasmid DNA encapsulated in the LDH@SiO(2) nanoparticles (pFDNA-LDH@SiO(2)-NPs) was prepared by the coprecipitation method, and the properties of pFDNA-LDH@SiO(2)-NPs were characterized by transmission electron microscopy, zeta potential analyzer, Fourier transform infrared spectroscopy, and X-ray diffraction analysis. The results demonstrated that the pFDNA-LDH@SiO(2)-NPs had a regular morphology and high stability with a mean diameter of 371.93 nm, loading capacity of 39.66%±0.45%, and a zeta potential of +31.63 mV. A release assay in vitro showed that up to 91.36% of the total plasmid DNA could be sustainably released from the pFDNA-LDH@SiO(2)-NPs within 288 hours. The LDH@SiO(2) nanoparticles had very low toxicity. Additionally, their high transfection efficiency in vitro was detected by fluorescent microscopy. Intranasal immunization of specific pathogen-free chickens with pFDNA-LDH@SiO(2)-NPs induced stronger cellular, humoral, and mucosal immune responses and achieved a greater sustained release effect than intramuscular naked plasmid DNA, and the protective efficacy after challenge with the strain F(48)E(9) with highly virulent (mean death time of chicken embryos ≤60 hours, intracerebral pathogenicity index in 1 -day-old chickens >1.6) was 100%. Based on the results, LDH@SiO(2) nanoparticles can be used as a delivery carrier for mucosal immunity of Newcastle disease DNA vaccine, and have great application potential in the future.